The Use of Artificial Intelligence in New Normal Era Against Pandemic COVID-19 in the Field of Health Services - Dian Agustin Wahjuningrum; Fery Setiawan; Setyabudi; Heni Puspitasari; Ahmad Yudianto; Agung Sosiawan; Arif Rahman Nurdianto; Swadheena Patro (Conservative Dentistry Journal, 2022)
Background: Indonesia is currently experiencing Coronavirus Disease-19 (COVID-19) pandemic which affects all sectors of life, therefore Indonesia is starting to prepare for New Normal era, including in health care sector. COVID-19 was previously known as novel Coronavirus Disease-19 (nCoV-19), where World Health Organization (WHO) declared it as a global pandemic in March 2020. New Normal era is an era of coexistence with COVID-19, resulting in new habits that were rarely or never practiced before. One practice that can be applied in health care sector is to use Artificial Intelligence (AI) to treat COVID-19 patients to prevent casualties for health workers. Health care providers are prone to contract aerosol and droplet transmission while treating patients, resulting in cytokine storm, acute respiratory distress syndrome (ARDS), and acute lung injury (ALI), which leads to death. Purpose: This mini review study used to explain the using of artificial intelligence in the new normal era against pandemic COVID-19 in the field of health services. Reviews: This pandemic COVID-19 restricts all of the communication between person to person. It also challenged the health service sector because the health service sector is the first line to combat the COVID-19. It is now popular to use artificial intelligence. This using can be used to help the health service sector in combating the COVID-19 pandemic especially in this new normal era. Conclusion: COVID-19 pandemic affects all aspects of life, especially health care sector, therefore AI use is important to prevent the deaths of health workers because of this pandemic.